2022
DOI: 10.1080/01652176.2022.2061744
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of seaweeds and their active compounds on animal health and production – a review

Abstract: Natural antioxidants applied as feed additives can improve not only animals’ health and overall performance but also increase their resistance to environmental stress such as heat stress, bad housing conditions, diseases, etc. Marine organisms, for example seaweeds – red, brown, and green macroalgae contain a plethora of biologically active substances, including phenolic compounds, polysaccharides, pigments, vitamins, micro- and macroelements, and proteins known for their antioxidant activity, which can help i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 125 publications
0
41
0
1
Order By: Relevance
“…Dietary seaweed ( Enteromorpha prolifera ) polysaccharide supplementation also improved broilers’ immunity and breast muscle growth ( Zhao et al, 2021 ). The phenolic compounds in brown seaweed can protect the body against oxidative damage that occurs in response to environmental or nutrient changes ( Li et al, 2017 ) and promote good health and productivity in animals ( Michalak et al, 2022 ). Previous studies showed that the dietary supplementation of marine algae polysaccharides extracted from seaweed ( E. prolifera ) improved bursa weight, the intestinal and liver antioxidant enzymes (total superoxide dismutase, glutathione, catalase and glutathione peroxidase) and reduced malondialdehyde ( MDA ) contents of broilers ( Liu et al, 2020b ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary seaweed ( Enteromorpha prolifera ) polysaccharide supplementation also improved broilers’ immunity and breast muscle growth ( Zhao et al, 2021 ). The phenolic compounds in brown seaweed can protect the body against oxidative damage that occurs in response to environmental or nutrient changes ( Li et al, 2017 ) and promote good health and productivity in animals ( Michalak et al, 2022 ). Previous studies showed that the dietary supplementation of marine algae polysaccharides extracted from seaweed ( E. prolifera ) improved bursa weight, the intestinal and liver antioxidant enzymes (total superoxide dismutase, glutathione, catalase and glutathione peroxidase) and reduced malondialdehyde ( MDA ) contents of broilers ( Liu et al, 2020b ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study used fermentation technology to treat Laminaria japonica and confirmed that fermentation can improve the utilization of active substances and increase anti-inflammatory activity. We compared Laminaria japonica alcoholic extracts with anti-inflammatory activity and found that LJ-G and LJ-Y could exert better anti-inflammatory and skin barrier repair effects [ 16 ]. Compared with the alcoholic extraction process, the Laminaria japonica extracts obtained using the fermentation method have a high extraction rate, high safety and high eco-friendliness that traditional organic solvent extraction lacks.…”
Section: Discussionmentioning
confidence: 99%
“…Laminaria japonica , also known as brown seaweed, is common in East Asian countries such as China, Japan and South Korea as a traditional Chinese medicinal and edible algae [ 15 ]. It is rich in active substances, such as fucoidan, fucoxanthin, dietary fiber, and carotenoids, and possesses significant antioxidant [ 15 ], anti-inflammatory [ 16 ], anti-aging and antibacterial properties [ 17 ]. Studies have confirmed that Laminaria japonica specifically inhibits the nuclear translocation of the STAT1 gene through the MAPK pathway, reduces skin inflammation and the expression level of cellular inflammatory chemokines, and inhibits the loss of skin moisture in mice caused by dinitrochlorobenzene (NC/Nga) sensitization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of fucoidan on animal health is through modulating the gut environment for the growth of beneficial gut microflora, stimulating the innate immune system and reducing the risk of diarrhea [ 132 ]. The commercially marketed algal products TascoTM from A. nodosum and Ocean FeedTM (a blend of brown, green and red macroalgae) are used as animal feed additives to improve the performance and immune response [ 132 , 133 ].…”
Section: Food and Feed Applications Of Fucoidanmentioning
confidence: 99%